North‐South asymmetry in the modeled phytoplankton community response to climate change over the 21st century. Issue 4 (20th December 2013) - Marinov, Irina; Doney, Scott C.; Lima, Ivan D.; Lindsay, K.; Moore, J. K.; Mahowald, N.
Abstract [1] Here we analyze the impact of projected climate change on plankton ecology in all major ocean biomes over the 21st century, using a multidecade (1880–2090) experiment conducted with the Community Climate System Model (CCSM‐3.1) coupled ocean‐atmosphere‐land‐sea ice model. The climate response differs fundamentally in the Northern and Southern Hemispheres for diatom and small phytoplankton biomass and consequently for total biomass, primary, and export production. Increasing vertical stratification in the Northern Hemisphere oceans decreases the nutrient supply to the ocean surface. Resulting decreases in diatom and small phytoplankton biomass together with a relative shift from diatoms to small phytoplankton in the Northern Hemisphere result in decreases in the total primary and export production and export ratio, and a shift to a more oligotrophic, more efficiently recycled, lower biomass euphotic layer. By contrast, temperature and stratification increases are smaller in the Southern compared to the Northern Hemisphere. Additionally, a southward shift and increase in strength of the Southern Ocean westerlies act against increasing temperature and freshwater fluxes to destratify the water‐column. The wind‐driven, poleward shift in the Southern Ocean subpolar‐subtropical boundary results in a poleward shift and increase in the frontal diatom bloom. This boundary shift, localized increases in iron supply, and the direct impact of warming temperatures on phytoplankton growth result in diatom increases in the Southern Hemisphere. An increase in diatoms and decrease in small phytoplankton partly compensate such that while total production and the efficiency of organic matter export to the deep ocean increase, total Southern Hemisphere biomass does not change substantially. The impact of ecological shifts on the global carbon cycle is complex and varies across ecological biomes, with Northern and Southern Hemisphere effects on the biological production and export partially compensating. The net result of climate change is a small Northern Hemisphere‐driven decrease in total primary production and efficiency of organic matter export to the deep ocean.